Cudrania tricuspidata leaves extract and its inhibitory activity against HFD-induced obesity in zebrafish (danio rerio) - Van Cuong, Tran; Nguyen Thi, Thoa (Tay Nguyen Journal of Sciences, 2023)
The research on screening active ingredients from natural resources that effectively for the treatment of metabolic disorders such as obesity and diabetes has received much attention recently. In this study, the compounds extracted from Cudrania tricuspidata (CT) leaves were analyzed through FT-IR, HPLC and GC-MS methods. The results showed that 50% ethanol extract (EtOH50) from CT leaves contains several bio-active substances such as catechins, quercetin, gallic acid, etc. In addition, to evaluate the obesity-preventing activity of the extract, an obesity model in adult zebrafish by high-fat diet was carried out. As the results, EtOH50 extract of CT leaves has good efficacy in preventing weight gain, regulating BMI and hyperglycemia in zebrafish. At the same time, based on qRT-PCR results have confirmed that the anti-obesity effect of CT leaves extract via the modulation of several biomarkers related to lipid metabolism, energy expenditure, cytokines genes. Taken together, these data suggest that Cudrania tricuspidata (CT) leaves can be developed as a treatment for obesity.